A Cross Sectional Study to Assess Liver Fibrosis in Patients with Diabetes and Metabolic Syndrome in India (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: liver fibrosis; enhanced liver fibrosis; non alcoholic fatty liver disease; cirrhosis; NAFLD fibrosis score